2018
DOI: 10.1002/cbin.10995
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐1 overexpression increases chemosensitivity of non‐small cell lung cancer cells by inhibiting autophagy related 3‐mediated autophagy

Abstract: Non-small cell lung cancer (NSCLC) is a major type of lung cancer. Drug resistance is a enormous obstacle for cancer treatment. Copious microRNAs (miRNAs) have been demonstrated to be implicated in drug resistance in NSCLC. In the present study, RT-qPCR assay revealed that microRNA-1 (miR-1) expression was downregulated in DDP resistant NSCLC tissues and cells. Western blot assay presented a remarkable increase of LC3B-II/LC3B-I ratio and a notable decline of p62 level in DDP resistant NSCLC cells, while these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 35 publications
2
23
1
1
Order By: Relevance
“…indeed, the data from the present study showed that paclitaxeland ddP-induced apoptosis was increased in Bc cells that overexpressed mir-1. Similar the current study, Hua et al (31) reported that mir-1 overexpression improved ddP sensitivity by inhibiting aTG3-mediated autophagy in non-small cell lung cancer cells. Thus, mir-1 may have a role in the treatment of Bc patients who are administered paclitaxel and ddP, but the specific mechanism requires further investigation in the future.…”
Section: Discussionsupporting
confidence: 89%
“…indeed, the data from the present study showed that paclitaxeland ddP-induced apoptosis was increased in Bc cells that overexpressed mir-1. Similar the current study, Hua et al (31) reported that mir-1 overexpression improved ddP sensitivity by inhibiting aTG3-mediated autophagy in non-small cell lung cancer cells. Thus, mir-1 may have a role in the treatment of Bc patients who are administered paclitaxel and ddP, but the specific mechanism requires further investigation in the future.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequent promotion of cell survival can be inhibited by knockdown of Atg5, an important regulator of autophagosome formation (46,47,55). Evidence further suggests a protective role for autophagy regulators ATG3, 5, 6, 7, and 12 in resistant cells, however, detailed mechanisms are not yet fully understood and hence require further studies (56)(57)(58)(59)(60). Interestingly, besides TFEB-regulated lysosomal alterations upon treatment with cytostatics, TFEB also contributes to cell survival by mechanisms independent of the aforementioned.…”
Section: Tfeb Signaling Regulating Drug Resistancementioning
confidence: 99%
“…Recently, the regulation of autophagy by miR-NAs has been shown to be a potentially effective strategy to reduce cancer cell chemoresistance [34]. Regarding NSCLC, while some studies have revealed a potential role of miRNAs and autophagy in cisplatin resistance in NSCLC [35,36], no investigations have verified the ability of miR-223 and FBXW7 to directly impact the regulation of autophagy and cisplatin resistance in NSCLC cells. Therefore, additional studies are required to elucidate the relationship between miRNAs, autophagy, and cisplatin resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%